INTEGRASI BUDAYA LOKAL DAN LINGKUNGAN DALAM KEGIATAN PASRAMAN KILAT DAN EDUKASI SAMPAH DI SD NEGERI 4 PEGUYANGAN, DENPASAR - Anak Agung Komang Suardana; Ni Wayan Nia Cahyani; Ni Ketut Rusmiyanti Cahyani; I Made Kerta Jaya; Ida Ayu Made Dwi Cempaka; I Putu Julio Andhika Putra (JURNAL SEWAKA BHAKTI, 2026)
The increasingly alarming waste management crisis in Indonesia, particularly in Bali, requires an educational approach based on community and local wisdom. This article describes the implementation of the Thematic Community Service Program (KKN) by Group 12 students from the Indonesian Hindu University (UNHI) at Peguyangan 4 Elementary School, which integrates environmental education with local cultural values ​​through the "Pasraman Kilat and Waste Education" activity. The methods used are participatory, educational, and demonstrative within a Community Development approach. The Pasraman Kilat activity emphasizes the values ​​of Tri Hita Karana, particularly the Palemahan aspect, through cultural practices such as the creation of ceremonial structures and Balinese dance training. Meanwhile, waste education focuses on understanding the 3Rs (Reduce, Reuse, Recycle), waste sorting, and recycling skills. The results of the activity show a significant increase in students' awareness, knowledge, and skills regarding waste management, as well as the strengthening of character based on local culture. This program has proven effective as a contextual and sustainable learning model that can be replicated in other elementary schools to foster environmentally conscious behavior from an early age.